1997
DOI: 10.1159/000127182
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Three Acute Stressors on the Serotonin 5-HT<sub>1A</sub> Receptor System in Rat Brain

Abstract: The effects of different acute stressors on circulating corticosterone levels, 5-HT 1A receptors and 5-HT1A mRNA levels were measured in male Sprague-Dawley rats. Two hours restraint stress, short swim stress (15 min) and long swim stress (30 min) increased circulating corticosterone levels 10-, 13- and 18-fold, respectively, when measured immediately after termination of the stress. Each stressor produced a unique profile of changes in 5-HT1A receptors measured in coronal sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…The present study showed that repeated treatment with a high dose of corticosterone, which induced a persistent elevation of blood level of this hormone (20.5-59.2 µg/dl), comparable to those (41.5-75.3 µg/dl) observed in severeto-moderate stress (Raghupathi and McGonigle 1997), produced functional subsensitivity of 5-HT 1A receptors in the CA1 region of the hippocampus. Corticosterone treatment did not affect significantly the passive membrane properties, such as resting membrane potential, membrane resistance and cell rectification, recorded before 8-OH-DPAT administration, thus ruling out the possibility that effects on these membrane properties contribute importantly to the observed results.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The present study showed that repeated treatment with a high dose of corticosterone, which induced a persistent elevation of blood level of this hormone (20.5-59.2 µg/dl), comparable to those (41.5-75.3 µg/dl) observed in severeto-moderate stress (Raghupathi and McGonigle 1997), produced functional subsensitivity of 5-HT 1A receptors in the CA1 region of the hippocampus. Corticosterone treatment did not affect significantly the passive membrane properties, such as resting membrane potential, membrane resistance and cell rectification, recorded before 8-OH-DPAT administration, thus ruling out the possibility that effects on these membrane properties contribute importantly to the observed results.…”
Section: Discussionsupporting
confidence: 71%
“…This dose yielded blood levels comparable to those obtained by Karten et al (1999) in their electrophysiological study showing decreased responsiveness of 5-HT 1A receptors. Similar levels are also induced by different stressors that modulate of 5-HT 1A receptor expression in the hippocampus (Raghupathi and McGonigle 1997). Since electrophysiological studies have evaluated the effect of corticosterone on 5-HT 1A receptor responsiveness elicited by the endogenous agonist 5-HT (Karten et al 1999), we decided to confirm and extend those results and to examine the effect of repeated treatment with corticosterone on the reactivity of CA1 neurons to (±)-8-hydroxy-2-di-N-propylamino)tetralin hydrobromide (8-OH-DPAT), a selective agonist at 5-HT 1A receptors.…”
Section: Introductionmentioning
confidence: 76%
“…Acute stress either increases or decreases hippocampal and/or cortical 5-HT 1A receptor binding in a stressorand subregion-dependent manner (Raghupathi and McGonigle 1997), providing support for specificity. This result is noteworthy given the belief that stressors need to be administered repeatedly to observe a (glucocorticoid-dependent) decrease in 5-HT 1A receptor binding, especially in the hippocampus (Flügge 1995, but see Mendelson andMcEwen 1991).…”
Section: -Ht 1a Receptors and Stressmentioning
confidence: 87%
“…Both a decrease (Chalmers et al 1993) as well as no change in 5-HT 1A receptor number in the CA1 subfield have been reported following treatment with high doses of corticosterone (Kuroda et al 1994;Mendelson and McEwen 1992). Chronic stress increases, decreases or has no effect on 5-HT 1A receptor levels, depending on the nature of the stress paradigm (Fernandes et al 1997;Kuroda et al 1994;Mendelson and McEwen 1992;Raghupathi and McGonigle 1997).…”
Section: Discussionmentioning
confidence: 99%
“…GR occupancy increases from 10% at the circadian trough to 80% at the circadian peak or following a stressful stimulus (Akana et al 1988;Reul et al 1987a). Stress produces plasma corticosterone levels in the range of 20-75 g/dl depending on the type of stressor (Bhatnagar et al 1997;Dallman et al 1994;Galea et al 1997;Groenink et al 1996;Kirby and Lucki 1998;Liberzon et al 1997;Mendelson and McEwen 1992;Raghupathi and McGonigle 1997). In pathophysiological states, such as chronic stress or depression, basal plasma cortisol levels are elevated (Dinan 1996).…”
mentioning
confidence: 99%